Nutritional Status of Hospitalized Stroke Patients: Assessment by Body Mass Index and Subjective Global Assessment Method - Gloria Kartika; Lisda Amalia; Gaga Irawan Nugraha (Althea Medical Journal, 2017)
Background: Stroke is a disease with a high mortality rate and common cause of disability. Nutritional factors are strongly associated with this disease. Malnutrition in hospitalized patients increases the incidence of complications, prolonged the length of stay and also the cost of hospitalization. Furthermore, nutritional status of stroke patients can deteriorate during hospitalization. The prevalence of malnutrition in hospitalized stroke patients is about 6% to 62%. The objective of this study was to identify  the nutritional status of hospitalized stroke patient.Methods: This was a descriptive cross-sectional study. Population of the study was hospitalized stroke patients at Neurology Ward, Kemuning Building Dr. Hasan Sadikin General Hospital Bandung, Indonesia from August until October 2014 who meet the inclusion criteria. Nutritional status was measured objectively using Body Mass Index (BMI) and subjectively using Subjective Global Assessment (SGA) method. The collected data were processed using  frequency tabulation and percentage.Results: Twenty six hospitalized stroke patients were included in this study. The hospitalized patients with normal BMI were about 12 people (46.15%), 8 people were overweight (30.77%), 4 people were undernourished (15.39%) and 2 people (7.69%) were obese. According to SGA measurement, approximately 18 people (69.22%) were moderately malnourished, and as much as 4 people (15.39%) were in good nutrition, whereas 4 people (15.39%) were severely malnourished.Conclusions: Majority of the hospitalized stroke patients has normal BMI and moderately malnourished based on SGA. DOI: 10.15850/amj.v4n2.1090